Pembrolizumab-induced donor duodenum perforation after remote simultaneous pancreas-kidney transplant: a case report and literature review - Kasra Shirini; Cinthia Drachenberg; Raphael P. H. Meier (Renal Replacement Therapy)
Abstract This case report describes a patient in their 60s, a simultaneous kidney and pancreas transplant recipient, who presented with severe allograft rejection following a single dose of the programmed cell death protein 1 (PD-1) inhibitor pembrolizumab for recurrent basal cell carcinoma (BCC) two decades posttransplant. The patient’s BCC had been treated with sonidegib for 6 years, and he had been off of immunosuppression for 8 years. The patient was back on insulin therapy and had resumed maintenance hemodialysis a few months before admission. A total of 6 weeks after receiving pembrolizumab, the patient was hospitalized with abdominal pain. Imaging, followed by surgical exploration, revealed a well-circumscribed small bowel perforation corresponding to the disappearance of the rejected donor duodenal patch, which was associated with the severely atrophic and fibrotic pancreas, while the kidney exhibited gross features of rejection. Histological evaluation confirmed extensive hemorrhagic necrosis and transmural necrotizing vasculitis with thrombosis in the duodenal patch. In addition, the renal parenchyma exhibited extensive hemorrhagic necrosis and multiple vessels with thrombosis. This case underscores the risks of the rupture/leakage of donor-derived tissue triggered by immune checkpoint inhibitors, and potentially any “provoked” rejection, in transplant patients who have remaining allografts in place.